Understanding subcortical projections to the lateral posterior thalamic nucleus and its subregions using retrograde neural tracing - Nakamura, Hisashi; Ohta, Keisuke (Frontiers in Neuroanatomy, 2024)
The rat lateral posterior thalamic nucleus (LP) is composed of the rostromedial (LPrm), lateral (LPl), and caudomedial parts, with LPrm and LPl being areas involved in information processing within the visual cortex. Nevertheless, the specific differences in the subcortical projections to the LPrm and LPl remain elusive. In this study, we aimed to reveal the subcortical regions that project axon fibers to the LPl and LPrm using a retrograde neural tracer, Fluorogold (FG). After FG injection into the LPrm or LPl, the area was visualized immunohistochemically. Retrogradely labeled neurons from the LPrm were distributed in the retina and the region from the diencephalon to the medulla oblongata. Diencephalic labeling was found in the reticular thalamic nucleus (Rt), zona incerta (ZI), ventral lateral geniculate nucleus (LGv), intergeniculate leaflet (IGL), and hypothalamus. In the midbrain, prominent labeling was found in the periaqueductal gray (PAG) and deep layers of the superior colliculus. Additionally, retrograde labeling was observed in the cerebellar and trigeminal nuclei. When injected into the LPl, several cell bodies were labeled in the visual-related regions, including the retina, LGv, IGL, and olivary pretectal nucleus (OPT), as well as in the Rt and anterior pretectal nucleus (APT). Less labeling was found in the cerebellum and medulla oblongata. When the number of retrogradely labeled neurons from the LPrm or LPl was compared as a percentage of total subcortical labeling, a larger percentage of subcortical inputs to the LPl included projections from the APT, OPT, and Rt, whereas a large proportion of subcortical inputs to the LPrm originated from the ZI, reticular formation, and PAG. These results suggest that LPrm not only has visual but also multiple sensory-and motor-related functions, whereas the LPl takes part in a more visual-specific role. This study enhances our understanding of subcortical neural circuits in the thalamus and may contribute to our exploration of the mechanisms and disorders related to sensory perception and sensory-motor integration.